Scaffolding Clinical Reasoning of Health Care Students: A Qualitative Exploration of Clinicians' Perceptions on an Interprofessional Obstetric Ward. (February 2020) - Visser, Cora LF; Wouters, Anouk; Croiset, Gerda; Kusurkar, Rashmi A
Purpose: Interprofessional education (IPE) on a ward supports students to generate interprofessional patient care plans as a means to learn about the roles, responsibilities, and clinical reasoning of other professions. We investigated how clinicians guide the clinical reasoning of students from their own and other professions and whether clinicians from nursing, midwifery, and medicine could scaffold students from all professions, that is, by providing just-in-time and tailored support. Methods: Nine supervising clinicians from medicine, nursing, and midwifery were interviewed and a repeat interview held 3 to 15 weeks later; one nurse supervisor was interviewed only once. Using conventional content analysis, themes were identified inductively. Next, we applied an existing scaffolding framework to conceptualise how clinicians supported the clinical reasoning in an IPE setting. Results: Themes were clinicians' interventions and intentions, results of interventions and of IPE, characteristics of students and clinicians, interactions between clinicians and students, and logistics. Clinicians applied various interventions and expressed several intentions to guide the learning of students from all professions. Clinicians stimulated students' clinical reasoning by structuring meetings, asking students to explain their thoughts to each other and through giving group assignments. Thus, clinicians used peer-assisted learning for the students. By collaborating with other supervising clinicians regarding the form and amount of guidance to give to the students, clinicians applied peer-assisted learning for themselves as well. Conclusion: Clinicians can learn to scaffold the clinical reasoning of students from different professions, when they are provided with training, good examples, and structures. An existing scaffolding framework can serve as an overview of aims and interventions to provide just-in-time guidance to students from all professions. The scaffolding framework is useful for training clinicians and for depicting the pedagogical approach for IPE wards.